Influence of Vibration Isolator Failure on Vehicle Operation Performance and Floating Slab Track Structure Vibration Reduction Effectiveness - Caiyou Zhao; Dongya Liu; Xiaoming Zhang; Qiang Yi; Liuchong Wang; Ping Wang (Shock and Vibration)
At present, steel-spring floating slabs have been widely used in urban rail transit to reduce the influence of ground vibration caused by vehicle operation on the surrounding environment. As a core part of vibration reduction for floating slab track, the steel-spring vibration isolator may fail in different forms during operation. In order to study the influence of vibration isolator failure on vehicle operation performance and floating slab track structure vibration reduction effectiveness, a rigid-flexible coupling dynamic model of vehicle-rail-floating slab track is established by multibody dynamics and finite element simulation, and the rationality of the model and its parameters is verified by comparing the theoretical calculation results with the measured data. Based on the model, the failure conditions of steel spring are simulated, considering the failure position and number of steel springs. The results show that the failures of steel-spring vibration isolators have a significant impact on operating safety and stability of vehicle, and the failure at end is more dangerous than that at midspan. In addition, it also changes the local restraint state of floating slab, resulting in the local vibration mode, which reduces the floating slab track structure vibration reduction effectiveness, mainly within 10 Hz. The different numbers of steel-spring failures will change the natural modal frequency of floating slab to varying degrees, which may cause the resonance of a certain frequency of the vehicle-track coupling system, leading to other track structure diseases.